2023
DOI: 10.1017/s0033291723000867
|View full text |Cite
|
Sign up to set email alerts
|

Depression and risk of gastrointestinal disorders: a comprehensive two-sample Mendelian randomization study of European ancestry

Abstract: Background Major depressive disorder (MDD) is clinically documented to co-occur with multiple gastrointestinal disorders (GID), but the potential causal relationship between them remains unclear. We aimed to evaluate the potential causal relationship of MDD with 4 GID [gastroesophageal reflux disease (GERD), irritable bowel syndrome (IBS), peptic ulcer disease (PUD), and non-alcoholic fatty liver disease (NAFLD)] using a two-sample Mendelian randomization (MR) design. Methods We obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 82 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…The 16 FRGs identified in this study are widely implicated in various metabolic pathways, such as “metabolism of alpha-linolenic acid,” “fat cell differentiation,” “regulation of fat cell differentiation,” and “circadian rhythm genes.” Notably, these genes have been linked to the causes of NASH, such as “fatty liver disease,” “dyslipidemias,” “insulin resistance,” “gestational diabetes,” and “unipolar depression” [ 37 41 ]. Sixteen FRGs were processed further.…”
Section: Discussionmentioning
confidence: 99%
“…The 16 FRGs identified in this study are widely implicated in various metabolic pathways, such as “metabolism of alpha-linolenic acid,” “fat cell differentiation,” “regulation of fat cell differentiation,” and “circadian rhythm genes.” Notably, these genes have been linked to the causes of NASH, such as “fatty liver disease,” “dyslipidemias,” “insulin resistance,” “gestational diabetes,” and “unipolar depression” [ 37 41 ]. Sixteen FRGs were processed further.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, these 16 genes exhibited a predilection for pathways pertinent to metabolism, encompassing domains such as "metabolism of alpha-linolenic acid", "fat cell differentiation", "regulation of fat cell differentiation", and "Circadian rhythm genes". Intriguingly, these genes demonstrated conspicuous links to the underpinnings and determinants of NASH, encapsulated by associations with conditions such as "fatty liver disease", "dyslipidemias", "insulin resistance", "gestational diabetes", and "unipolar depression" [36][37][38][39][40]. Furthermore, an endeavor was undertaken to discern the quintessential ferroptosis-related hub genes in NASH, employing 113 machine-learning algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies have primarily focused on a single type of gastrointestinal disease, such as IBD ( Yang et al, 2023 ) or IBS ( Zhang et al, 2024 ). There are also some contradictory results, for instance, Youjie Zeng and others demonstrated that anxiety and depression do not increase the risk of gastroesophageal reflux disease ( Zeng et al, 2023 ), while other experiments have arrived at the opposite conclusion ( Chen et al, 2023 ; Zou et al, 2023 ). Therefore, in order to more comprehensively explore the potential relationship between the two, we have selected a broader range of psychiatric diseases and gastrointestinal diseases, as well as multiple datasets that differ from those used in previous studies, to provide more robust evidence.…”
Section: Introductionmentioning
confidence: 99%